THE CROWDFUNDING TECHNOLOGY IN DEVELOPMENT OF THE NATIONAL TOURISM SYSTEM - M. G. Boiko; N. I. Vedmid; A. G. Okhrimenko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2017)
The article substantiates the sense of crowdfunding and determines a list of participants of crowdfunding projects. The author has proposed a scheme for implementation of a crowdfunding tourism project, indicating the main stakeholders. The author has substantiated directions of implementation of projects, using crowdfunding in the national tourism system. The author has suggested a “house” of crowdfunding for projects of the national tourism system. The article determines advantages and disadvantages of crowdfunding for the main stakeholders and the society.